Pengembangan Media Interaktif Berbasis Appypie dalam Model Problem Based Learning untuk Meningkatkan Minat Belajar Peserta Didik pada Materi Larutan Penyangga - Rahmawati, Rahmawati; Danial, Muhammad; Wijaya, Mohammad (Program Pasca Sarjana UNM, 2024)
This Study is a development research that aims to produce interactive media based on appypie reality in a valid, practical, annd effective pronlem based learning model. The development model used is the ADDIE development model which consists of five stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The interactive media based on appypie that was developed was validated by two experts. Then, it was tested to 29 students in grade XI MIA 3 SMAN 3 Pinrang. The analysis used is data analysis of validity, practicality and effectiveness. The interactive media based on appypie is stated to valid based on the result of validating interactive media based on appypie with an average value of the media expert of 3.76, which are in very valid category. The interactive media based on appypie is stated to be practical based on (1) the implementation of interactive media with an average total percentage of 95,60%, which is in very high category; (2) the teacher's response with an average score of 95,75%, which is in very practical category; and (3) the students’ responses with an average score of 88,25%, which is in very practical category. The interactive media is stated to be effective based on the results of the analysis of the learning outcomes test and analysis of learning interest questionnaires with a class completeness percentage of 84% and an average value of the percentage of learning interest assessment of 81%, which is in high category. Therefore, the results of the study indicate that interactive media based on appypie in the proble, based learning learning model has valid, practical, and effective qualities.